'Slowing down the going-away process' — Tom Stoppard and Soviet Dissent. Issue 4 (1st October 2016) - Hurst, Mark
Abstract: Tom Stoppard is a playwright most noted for his ferocious wordplay and playful approach to reality. In the 1970s and 1980s, his concern for like-minded prisoners of conscience in the Soviet bloc informed his activism on their behalf, utilising his public profile in an attempt to reposition their plight in the West. Stoppard's activism was largely informed by his involvement with a number of non-governmental organisations (NGOs) working to publicise human rights violations in the Soviet Union, who provided him with the most up to date information on these abuses, and gave him access to dissidents. This article explores Stoppard's activism on behalf of Soviet prisoners of conscience, highlighting the impact that these organisations had on his activism. Through an assessment of Stoppard's efforts, it highlights the important role that NGOs and celebrity politics played during the cold war.